United Nations Convention on the Rights of Child: Forced Conversion of Hindu Minor Girls in Pakistan - Ali, Muhammad Imran (Journal of Legal Studies, 2021)
Pakistan has ratified the United Nations Convention on the Rights of Child expressing therein that the right to freedom of religion incorporates that nobody ought to be compelled to change his religion. Pakistan’s constitution guarantees religious freedom to all minority communities in Pakistan. Forced conversion to Islam has become another type of rough fanaticism in Pakistan. Constrained transformation is the point at which an individual who uses pressure, power, intimidation, or danger to drive someone else to acknowledge another religion. It influences almost all minority groups in Pakistan, but the biggest victims are Hindu minor girls in Sindh province. It should be forbidden to pursue a position of power to entice vulnerable Hindu minor girls to convert under duress. As the criminal justice system in Pakistan is not addressing this issue effectively, legislation is urgently needed to protect vulnerable children. This article focuses on the need to promulgate a law providing forcible conversion of Hindu minor girls as a criminal offense. A literature review method is adopted for this paper.